Desenvolvimento de peptídeos miméticos de antígenos do M. leprae e implicações no diagnóstico e prognóstico da hanseníase - Lima, Mayara Ingrid Sousa (2015)
Early diagnosis of leprosy is an important contribution to reducing the incidence of the disease. For its early detection, the development of new platforms that include the mapping of antigens with potential to be used in immunodiagnostic is of great interest. Among these antigens, the PGL-1 and epitopes derived from specific bacillus proteins have received great attention. Alternatively, due to their versatility to perform the same functions as the protein and non-protein natural antigens, mimetic peptides are considered an important tool. Thus, our goal was to produce mimetic peptides of Mycobacterium leprae antigens that are promising as serological markers, which will be explored in new diagnostic platforms. To produce peptide mimetics, phage display technology was used. In the first case, we used a monoclonal anti-PGL-1 (CS-38) aiming to obtain peptides that mimics the PGL-1. In the second case, the peptides were obtained having purified IgGs from patients with leprosy as target. The sequences of the selected peptides expressed on the phage surface were chemically synthesized. The synthetic peptides were validated by ELISA (case 1 and 2) and by an immunosensor based on Surface Plasmon Resonance (case 1). Aiming to confirm and identify the targets of the mimetic peptides, scFv antibodies were produced by reverse engineering. The PGL-1-M3 peptide that mimics the native PGL-1 had a sensitivity of 89.11% and specificity of 100.00% in the IgM detection, with positivity of 100% in lepromatous (LL). The IgG detection had positivity of 60% for tuberculoid (TT) and 39% for household contacts (HC). This peptide was used in assembling one biophotonics platform, which allowed the differentiation of all forms of leprosy (p <0.05). The anti-scFv-M3 PGL-1 recognized native PGL-1 and accurately detected the M. leprae in immunohistochemistry tests. The MPML11, MPML14 and MPML12 peptides that mimics M. leprae antigens detect IgG and IgA in patients and HC. In IgG detection, MPML11 peptide showed positivity in 52.2% of TT and 35% of HC, and is also a promising marker of type 2 reaction. MPML12 and MPML14 peptides showed a very similar behavior to the PGL-1, with positivity of 100% and 92.85% in LL, respectively. The three peptides detected IgA in the serum of patients, especially multibacillary (MBs); and IgA in saliva of MBs and HC which index case was multibacillary. Mimetic peptides obtained in this work were confirmed as true mimetics of M. leprae antigens and can be applied in the diagnosis of leprosy in different platforms.